Profile Perusahaan dan Sustainability Disclosure Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Laksmi, Sagung Ayu Lira; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 34 No 9 (2024), 2024)
This study aims to determine the differences in sustainability report disclosure (sustainability disclosure) based on company profiles, namely high profile companies and low profile companies. The population in this research is all companies listed on the IDX for 2018-2020 which issued Sustainability Reports, namely 838 companies. This study uses a non-probability sampling method with a purposive sampling technique. This study uses the normality test, independent t test and Mann-Whitney U. The results of the research show that there are differences in the disclosure of sustainability reports between high profile companies and low profile companies on economic, social and overall indicators, but there are no differences in environmental indicators. The implications of this research produce a source of thought to become material for study for management to pay more attention to the disclosure of the Sustainability Report because currently information related to economic, social and environmental indicators has become one of the most important aspects of the sustainability of a company's survival. Keywords: Sustainability Report; Company Profile; High Profile; Low Profile